Endogenous dipeptide‐carnosine supplementation ameliorates hypobaric hypoxia‐induced skeletal muscle loss via attenuating endoplasmic reticulum stress response and maintaining proteostasis. Issue 1 (29th August 2021) - Agrawal, Akanksha; Rathor, Richa; Kumar, Ravi; Singh, Som Nath; Kumar, Bhuvnesh; Suryakumar, Geetha
Abstract: High altitude is an environmental stress that is accompanied with numerous adverse biological responses, including skeletal muscle weakness and muscle protein loss. Skeletal muscle wasting is an important clinical problem, progressing to critical illness, associated with increased morbidity and mortality. The present study explores the protective efficacy of endogenous dipeptide, carnosine (CAR), supplementation in ameliorating skeletal muscle protein loss under hypobaric hypoxia (HH). Male Sprague–Dawley rats ( n  = 5) were randomly divided into control group, HH‐exposed group (3 days HH exposure equivalent to 7, 620 m), and HH‐exposed rats supplemented with carnosine (3 days; 150 mg/kg b.w, orally) (HH + CAR). HH‐exposed rats supplemented with CAR ameliorated HH‐induced oxidative protein damage, lipid peroxidation, and maintained pro‐inflammatory cytokines levels. HH‐associated muscle protein degradative pathways, including calpain, ubiquitination, endoplasmic reticulum stress, autophagy, and apoptosis were also regulated in carnosine‐supplemented rats. Further, the muscle damage marker, the levels of serum creatine phosphokinase were also reduced in HH + CAR co‐supplemented rats which proved the protective efficacy of CAR against hypobaric hypoxia‐induced muscle protein loss. Altogether, CAR supplementation ameliorated HH‐induced skeletal muscle protein loss via performing multifaceted ways, mainly by maintaining redox homeostasis and proteostasis in skeletal muscle.